Faktor–Faktor yang Mempengaruhi Keputusan Wanita Muslim di Wilayah Tangerang Selatan Berwirausaha - Cut Erika Ananda Fatimah (Esensi: Jurnal Bisnis dan Manajemen, 2015)
This paper empirically examined the Analysis factors that influences of decisions to be Entrepreuner at Moslem Women Entrepreuner in South Region in Tanggerang. The analysis factors of influences of decisions factors is intended to determne whether among interests, motivations, families support, financial resources and information technology. The study utilizes a review of litelatures to purpose a conceptual model. The model is tested with data from survey among 60 moslem women in South region of Tanggerang using Factor Analysis Technique. The dimension of this The results confirm that the first factor is dominated by the internet facilities, social media, information technology expand the network and the use of information technology reduces the cost of the efforts of women entrepreneurs in the moslem women in South region of Tanggerang.DOI: 10.15408/ess.v5i2.2345